2010
DOI: 10.1007/s10658-010-9696-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and host specificity of Phytophthora citrophthora isolates causing branch cankers in Clementine trees in Spain

Abstract: Considerable tree losses have been observed during the past few years in Spain due to Phytophthora branch canker of clementines caused by Phytophthora citrophthora. The emergence of this disease led to the speculation that either the pathogen has evolved increasing its aggressiveness or specificity to clementines. A total of 134 isolates of P. citrophthora collected from 2003 to 2005 in 135 citrus orchards in Spain and 22 reference isolates were analyzed genotypically and phenotypically to determine the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 32 publications
(44 reference statements)
4
21
0
Order By: Relevance
“…and four out of seven citrus nurseries surveyed were contaminated with the pathogen (Wehner et al, 1986). Snails and ants can also serve as dispersal vectors of Phytophthora citrophthora (Alvarez et al, 2009). In South Africa, brown snails [Helix aspersa (Müller)] and dune snails [Theba pisana (Müller)], were identified in Clementine mandarin trees and their role as possible vectors are proposed as targets for future research.…”
Section: Discussionmentioning
confidence: 99%
“…and four out of seven citrus nurseries surveyed were contaminated with the pathogen (Wehner et al, 1986). Snails and ants can also serve as dispersal vectors of Phytophthora citrophthora (Alvarez et al, 2009). In South Africa, brown snails [Helix aspersa (Müller)] and dune snails [Theba pisana (Müller)], were identified in Clementine mandarin trees and their role as possible vectors are proposed as targets for future research.…”
Section: Discussionmentioning
confidence: 99%
“…These two putative taxa were reported to be reproductively and geographically isolated (Cohen et al 2003). Alvarez et al (2011) studied a collection of 134 P. citrophthora isolates from Spain with the same RAMS markers as Cohen et al (2003) and found 14 different genotypes (P-1-P-14) of which P-1, P-9 and P-12 respectively corresponded to G1, G3 and G2 of Cohen et al (2003). Multivariate analyses of morphological and physiological characteristics of isolates from the 14 genotypes indicated that P-12 (G2) isolates clustered separately from the remainder of the P. citrophthora genotypes, adding further support to the suggestion that the G2 group of Cohen et al (2003) represents a distinct species.…”
Section: Introductionmentioning
confidence: 97%
“…Phytophthora citrophthora (Smith and Smith) Leonian is a serious pathogen of citrus worldwide, causing root rot, trunk and branch cankers and brown rot of citrus fruit (Erwin and Ribeiro 1996, Maseko and Coutinho 2002, Dirac et al 2003, Schutte and Botha 2010, Alvarez et al 2011. Phylogenetically the pathogen fits into Phytophthora clade 2a sensu Blair et al (2008) based on the analyses of several nuclear (internal transcribed spacers [ITS], b-tubulin, 28S ribosomal DNA, 60S ribosomal protein, enolase, tigA, heatshock protein 90 and elongation factor 1-a) and mitochondrial (cytochrome c oxidase [COX] 1 and 2 and NADH dehydrogenase subunit 1) regions (Cooke et al 2000, Kroon et al 2004, Blair et al 2008.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations